Modelling regulatory capture in the port sector: A case study in the Philippines. Issue 2 (June 2022) - Ponio, Gideon; Rashed, Yasmine; van Hassel, Edwin; Verhoeven, Patrick
Highlights: Regulatory capture can cause inefficiency. Model the outcome of regulatory capture on technical efficiency using an error correction model. The port sector of the Philippines is used as a case. Capture, measured by corruption, has a long-term negative impact on efficiency. Decentralization and liberalization policy reforms can avert capture and corruption whilst boosting efficiency. Abstract: Public service sectors have been a common topic for the study of the theory of economic regulation due to the natural monopolistic tendencies they pose. The study attempts to model regulatory capture by examining the impact of regulation and corruption on efficiency in one of these public service sectors, the port sector. The empirical analysis focuses on the port sector of the Philippines and its central port authority, the Philippine Ports Authority. Employing a regression analysis on a limited time series dataset from 1990 to 2018, we show that, while controlling for relevant factors, corruption has significant negative influence on port efficiency.